Preparation method and application of injectable mussel shell polysaccharide hydrogel adhesive
By introducing mussel bionic modification and biposcoli cross -linking technologies in shell gel adhesives, the problem of poor biocompatibility and insufficient adhesion ability is solved, and high -efficiency adhesion and fast in the humid environment are realized in a humid environment. Consortium is suitable for a variety of trauma and injury.
Patent Information
- Application Number
- CN202310170300.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-02-27
AI Technical Summary
In the prior art, there are problems such as poor biocompatibility, slow crosslinking speed and inability to effectively adhere to the adhesive under wet conditions.
Prepare the carbon digo puppets to prepare the cat-CT-CS of almons of the migration shells, and prepare an injection-type imitation iconic gel adhesive through the biposcolic cross-linking method. This method includes dissolving CAT-CS in the ion water, formulating a temperature-sensitive polymer PNAM solution and NAHCO3 solution, adding it to the CAT-CS solution under the conditions of the ice water bath to form a hydrogel adhesive and frozen and dry.
The excellent adhesion performance, rapid cross -linking, bacteriostatic antibacterial and other characteristics under humid conditions are achieved. It is suitable for the treatment of traumatic closure and deep damage in the body and deep damage in the body.
Smart Images

Figure CN116328022B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical polymer material preparation, and in particular relates to a method for preparing an injectable mussel shellan-imitation hydrogel adhesive. The invention also relates to an application of the injectable mussel shellan-imitation hydrogel adhesive. Background Art
[0002] Every year, there are 114 million cases of tissue trauma caused by traumatic accidents, chronic trauma, and surgical incisions. Traditional suturing methods have disadvantages such as complex and time-consuming operations, easy to cause secondary damage, and need to be removed after surgery. They are also not suitable for complex and sensitive surgeries such as vascular suturing, eye surgery, and nerve repair. During the healing process, air and body fluid leakage can cause bacterial infection, which can even be life-threatening in severe cases. The development of new tissue adhesives to replace traditional suture materials has important theoretical significance and practical application value.
[0003] As a new type of tissue adhesive, hydrogel has a unique three-dimensional network structure, showing inherent flexibility, controllable mechanical strength and good biocompatibility. However, a large amount of water interacts with the hydrogel, which seriously weakens its adhesion ability. It is necessary to develop a new type of hydrogel as a tissue adhesive so that it has strong adhesion to the interface under wet conditions. Studies have found that marine mussels can firmly adhere to the surfaces of various materials under the constant scouring of waves. This super strong universal adhesion and wet adhesion ability is attributed to the adhesive protein secreted by the mussel. The main component is 3,4-dihydroxyphenylalanine, and the catechol group of its side chain plays a key role in the adhesion process, that is, underwater adhesion is achieved through hydrogen bonds, coordination, electrostatic interactions, cation-π interactions and π-π interactions.
[0004] Adhesion, high toughness and biocompatibility in body fluid environment are the challenges faced by medical tissue adhesives. However, most existing technologies are applied to skin surface wounds, and have the defects of weak wet adhesion ability, inability to repair deep wounds, and inability to be applied to sensitive or irregularly shaped parts, which greatly limits its application scope. Chitosan is currently the most commonly used natural polymer for preparing adhesives due to its inherent tissue adhesion, antibacterial hemostasis, non-toxicity, and biodegradability. Using mussel biomimetic modified chitosan as the matrix, an injectable mussel chitosan hydrogel adhesive is constructed, which has the characteristics of rapid cross-linking, antibacterial and antibacterial, and strong anti-wet adhesion ability; it can be used for wound closure on the tissue surface, and can also be used as an injection to treat deep injuries in the body. It has a wider range of applications and more obvious treatment effects. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which solves the problems of poor biocompatibility, slow cross-linking speed and inability of the adhesive to effectively adhere under humid conditions in the prior art.
[0006] Another object of the present invention is to provide an application of an injectable mussel shell polysaccharide hydrogel adhesive.
[0007] The first technical solution adopted by the present invention is a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which is specifically implemented according to the following steps:
[0008] Step 1, using chitosan CS as a matrix, and adopting a carbodiimide coupling method to prepare mussel biomimetic modified chitosan Cat-CS;
[0009] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS as monomers, a free radical solution polymerization method is used to prepare a thermosensitive polymer PNAM;
[0010] Step 3, dissolving Cat-CS in deionized water to prepare a mussel biomimetic modified chitosan Cat-CS solution, and then preparing a PNAM solution and a NaHCO3 solution; under ice water bath conditions, sequentially adding the PNAM solution and the NaHCO3 solution dropwise into the mussel biomimetic modified chitosan Cat-CS solution, continuously stirring, then placing in a constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0011] The first technical solution of the present invention is also characterized in that:
[0012] Step 1 is implemented according to the following steps:
[0013] Chitosan CS is dissolved in a hydrochloric acid solution and the pH is adjusted to 1.5-1.7, and then a sodium hydroxide solution is added to adjust the pH to 5.3-5.5 to obtain a solution A. 3,4-dihydroxyphenylacetic acid HCA is added to the solution A to obtain a solution B. 1-ethyl-(3-dimethylaminopropyl)carbodiimide EDC and N-hydroxysuccinimide NHS are dissolved in a mixed solvent C, and are added dropwise to the solution B under continuous stirring to fully react for 1-2 hours. The fully reacted solution is dialyzed, and finally freeze-dried at -40--50°C to obtain the mussel chitosan Cat-CS.
[0014] In step 1, the concentration of hydrochloric acid is 1 mol / L, and the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is composed of distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:1:1 to 1:2:8:8.
[0015] The dialysis conditions in step 1 are dialysis in a hydrochloric acid solution containing 100 mmol / L NaCl for 48 to 72 hours, the pH of the hydrochloric acid solution is 3 to 3.5, and then dialysis in deionized water for 4 to 8 hours. In step 1, the fully reacted solution is transferred to a dialysis bag with a molecular weight cutoff of 3500 to 5000 Da for dialysis.
[0016] Step 2 is implemented as follows:
[0017] The monomers N-isopropylacrylamide NIPAm and 2-acrylamido-2-methylpropanesulfonic acid AMPS are dissolved in a mixed solvent D, and the initiator is added dropwise under N2 protection and constant temperature stirring. The addition time is 2 to 3 hours and the reaction temperature is 55 to 65°C. After the addition is completed, 2 mL of initiator is added after reacting for 10 to 12 hours, and the reaction is continued for 10 to 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da, and finally freeze-dried at -40 to -50°C to obtain a thermosensitive polymer PNAM.
[0018] In step 2, the initiator is azobisisoheptanenitrile, and the mass of the initiator is 1% of the total mass of N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS monomers; the mixed solvent consists of deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0019] In step 3: the concentration of the mussel biomimetic modified chitosan Cat-CS solution is 10-35 mg / mL; the concentration of the NaHCO3 solution is 0.06-0.10 mol / L; the mass concentration of the PNAM aqueous solution is 2.0-6.0 mg / mL; the volume ratio of the mussel biomimetic modified chitosan Cat-CS solution, the PNAM solution and the NaHCO3 solution is 15:3:10.
[0020] In step 3, the temperature of the ice water bath is 0-4°C, the dropping speed is 0.5-1.0 μL / s, the stirring time is 1-2 hours, the freeze-drying temperature is -40--50°C, the freeze-drying time is 12-24 hours, and the gel time is 30-180 seconds.
[0021] The second technical solution adopted by the present invention is that the injectable mussel shell polysaccharide hydrogel adhesive is applied to wounds with irregular or sensitive surfaces, and is also applied as an injection to deep injuries.
[0022] The beneficial effect of the present invention is that the preparation method of the injectable mussel-like chitosan hydrogel adhesive uses chitosan as a matrix, synthesizes mussel biomimetic modified chitosan Cat-CS by carbodiimide coupling method, and has the advantages of antibacterial and sterilization, excellent adhesion strength and promotion of wound healing, and adopts a double ion crosslinking method to prepare the injectable mussel-like chitosan hydrogel adhesive. The hydrogel adhesive not only has good adhesion properties and is suitable for humid environments; it is also less toxic and safer, and can be applied to tissue repair and regeneration, antifouling and antibacterial, drug delivery, cell encapsulation and other fields; it is also temperature sensitive and can be positioned and injected into some tissues and organs, which can reduce secondary damage caused by surgery and reduce surgical costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure is a schematic diagram of the preparation process of the injectable mussel shell polysaccharide hydrogel adhesive of the present invention;
[0024] Figure 2 It is a SEM picture of the chitosan hydrogel adhesive prepared by the double ion crosslinking method in the preparation method of the injectable mussel-like chitosan hydrogel adhesive of the present invention;
[0025] Figure 3 It is a graph showing the adhesion strength of the hydrogel on different substrates in the method for preparing the injectable mussel shell polysaccharide hydrogel adhesive of the present invention;
[0026] Figure 4 This is a graph showing the effect of different NaHCO3 concentrations on the hydrogel adhesion strength in the preparation method of the injectable mussel shell polysaccharide hydrogel adhesive of the present invention;
[0027] Figure 5 This is a comparison chart of the adhesion of hydrogels with different grafting degrees to glass in the preparation method of the injectable mussel shell polysaccharide hydrogel adhesive of the present invention. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] The preparation method of the injectable mussel shell polysaccharide hydrogel adhesive of the present invention is as follows: Figure 1 As shown, the specific implementation steps are as follows:
[0030] Step 1, using chitosan CS as a matrix, and adopting a carbodiimide coupling method to prepare mussel biomimetic modified chitosan Cat-CS;
[0031] Step 1 is implemented according to the following steps:
[0032] Chitosan CS is dissolved in a hydrochloric acid solution, and the pH is adjusted to 1.5-1.7 to protonate chitosan and provide an acidic environment. Then, a sodium hydroxide solution is added to adjust the pH to 5.3-5.5 to obtain a solution A. 3,4-dihydroxyphenylacetic acid HCA is added to the solution A to obtain a solution B. 1-ethyl-(3-dimethylaminopropyl)carbodiimide EDC and N-hydroxysuccinimide NHS are dissolved in a mixed solvent C, and are added dropwise to the solution B under continuous stirring to fully react for 1-2 hours. The fully reacted solution is dialyzed, and finally, the mussel-like chitosan Cat-CS is obtained after freeze-drying at -40--50°C.
[0033] When the pH value of the system environment is higher than 5.5, catechol is oxidized to quinone. Considering the oxidizability of the catechol group during the reaction, the pH of the system is kept less than 5.5 throughout the process to avoid oxidation of the catechol group.
[0034] In step 1, the concentration of hydrochloric acid is 1 mol / L, and the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is composed of distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:1:1 to 1:2:8:8.
[0035] The dialysis conditions in step 1 are dialysis in a hydrochloric acid solution containing 100 mmol / L NaCl for 48 to 72 hours, the pH of the hydrochloric acid solution is 3 to 3.5, and then dialysis in deionized water for 4 to 8 hours. In step 1, the fully reacted solution is transferred to a dialysis bag with a molecular weight cutoff of 3500 to 5000 Da for dialysis.
[0036] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS as monomers, a free radical solution polymerization method is used to prepare a thermosensitive polymer PNAM;
[0037] Step 2 is implemented as follows:
[0038] The monomers N-isopropylacrylamide NIPAm and 2-acrylamido-2-methylpropanesulfonic acid AMPS are dissolved in a mixed solvent D, and the initiator is added dropwise under N2 protection and constant temperature stirring. The addition time is 2 to 3 hours and the reaction temperature is 55 to 65°C. After the addition is completed, 2 mL of initiator is added after reacting for 10 to 12 hours, and the reaction is continued for 10 to 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da, and finally freeze-dried at -40 to -50°C to obtain a thermosensitive polymer PNAM.
[0039] In step 2, the initiator is azobisisoheptanenitrile, and the mass of the initiator is 1% of the total mass of N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS monomers; the mixed solvent consists of deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0040] Step 3, dissolving Cat-CS in deionized water to prepare a mussel biomimetic modified chitosan Cat-CS solution, and then preparing a PNAM solution and a NaHCO3 solution; under ice water bath conditions, sequentially adding the PNAM solution and the NaHCO3 solution dropwise into the mussel biomimetic modified chitosan Cat-CS solution, continuously stirring, then placing in a constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0041] In step 3:
[0042] The concentration of mussel biomimetic modified chitosan Cat-CS solution is 10-35 mg / mL; the concentration of NaHCO3 solution is 0.06-0.10 mol / L; the mass concentration of PNAM aqueous solution is 2.0-6.0 mg / mL; the volume ratio of mussel biomimetic modified chitosan Cat-CS solution, PNAM solution and NaHCO3 solution is 15:3:10.
[0043] In step 3, the temperature of the ice water bath is 0-4°C, the dropping speed is 0.5-1.0 μL / s, the stirring time is 1-2 hours, the freeze-drying temperature is -40--50°C, the freeze-drying time is 12-24 hours, and the gel time is 30-180 seconds.
[0044] The injectable mussel shellan-like hydrogel adhesive is applied to wounds involving irregular or sensitive surfaces and is also applied as an injection to deep lesions.
[0045] The invention discloses a method for preparing an injectable mussel-like chitosan hydrogel adhesive. The method uses chitosan as a matrix and prepares mussel-like biomimetic modified chitosan Cat-CS through a carbodiimide coupling reaction. The injectable mussel-like chitosan hydrogel is prepared by a double ion crosslinking method, and can be injected in vivo, quickly gelled at body temperature, and has excellent adhesion performance.
[0046] Figure 1 The schematic diagram of the formation of the injectable mussel shell polysaccharide hydrogel adhesive of the present invention is shown in FIG. 1 . The gel temperature is 37° C. The hydrogel is in a solution state below the gel temperature and quickly forms a gel after reaching the gel temperature. Figure 2 This is a SEM image of the chitosan hydrogel adhesive prepared by the dual ion crosslinking method of the present invention; the freeze-dried hydrogel presents a dense three-dimensional porous network structure, and the dense network structure enables it to be widely used in the field of tissue adhesion. Figure 3The figure shows the adhesion strength of the hydrogel of the present invention on different substrates. The hydrogel has the strongest adhesion strength to galvanized iron, forming a stable organic metal complex on the surface of the material through strong hydrogen bonds; followed by different degrees of adhesion to glass, PMMA and pig skin surfaces, which is attributed to non-covalent interactions (such as hydrogen bonds, ionic bonds and cation-π interactions). Figure 4 Graph showing the effect of different NaHCO3 concentrations on the adhesion strength of hydrogels according to the present invention; Figure 4 It can be seen that the increase in NaHCO3 content improves the adhesion strength of the hydrogel, because NaHCO3 increases the interaction with the amino groups of Cat-CS to form a tighter chelating network. Figure 5 is a comparative diagram of the adhesion of the hydrogels with different grafting degrees to glass according to the present invention, using Figure 5 It can be seen that the adhesion strength of the hydrogel adhesive increases with the increase of the grafting degree, indicating that the catechol group is the main factor affecting the adhesion strength, and the adhesion strength between the hydrogel and the substrate can be improved by increasing the catechol grafting degree.
[0047] Example 1
[0048] The present invention relates to a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which is specifically implemented according to the following steps:
[0049] Step 1, dissolve chitosan CS in a hydrochloric acid solution with a pH of 1.6, and add a certain concentration of hydrochloric acid to adjust the pH of the system back to 1.6, so that the chitosan is protonated and an acidic environment is provided, and then add a sodium hydroxide solution to adjust the pH of the system to 5.4 to obtain solution A. Add 3,4-dihydroxyphenylacetic acid HCA to solution A to obtain solution B. Dissolve EDC and NHS in a mixed solvent C composed of distilled water and anhydrous ethanol, and add them dropwise to the above solution B under continuous stirring, ensuring that the pH of solution B is less than 5.5 throughout the process, fully react for 1 hour, transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 3500Da for dialysis, and finally freeze-dry the sample at -50°C to obtain the mussel chitosan Cat-CS.
[0050] The concentration of hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:1:1; the degree of grafting of catechol is 2.8%;
[0051] The dialysis conditions were as follows: dialysis in a hydrochloric acid solution with a pH of 3 and containing 100 mmol / L NaCl for 48 h, and then dialysis in deionized water for 4 h.
[0052] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS free radical polymerization to prepare thermosensitive polymer PNAM; specifically: dissolve monomers NIPAm and AMPS in mixed solvent D, then add the initiator dropwise to the mixed solvent D under N2 protection and constant temperature stirring at 60°C for 2 hours; after the addition is complete, react for 12 hours, then add 2 mL of initiator, and continue to react for another 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da, and finally freeze-dried at -50°C to obtain the thermosensitive polymer PNAM.
[0053] The initiator is azobisisoheptanonitrile, the mass of the initiator is 1% of the total mass of the monomers, and the mixed solvent D is deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0054] Step 3, dissolving Cat-CS in deionized water to prepare a Cat-CS solution, preparing a PNAM solution and a NaHCO3 solution; under ice-water bath conditions, sequentially adding PNAM and NaHCO3 solution dropwise to the Cat-CS solution, and stirring for 1 hour, then placing it in a 37°C constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0055] The concentration of Cat-CS solution is 20 mg / mL; the concentration of NaHCO3 solution is 0.06 mol / L; the mass concentration of PNAM aqueous solution is 3.0 mg / mL; the volume ratio of Cat-CS, PNAM and NaHCO3 solution is 15:3:10; the dropping speed is 0.6 μL / s.
[0056] The temperature of the ice water bath was 1°C, the freeze drying temperature was -50°C, the freeze drying time was 10 h, the gel time was 120 s, and the adhesion strength was 69 kPa.
[0057] Example 2
[0058] The present invention relates to a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which is specifically implemented according to the following steps:
[0059] Step 1, dissolve chitosan CS in a hydrochloric acid solution with a pH of 1.5, and add a certain concentration of hydrochloric acid to adjust the pH of the system back to 1.5, so that the chitosan is protonated and an acidic environment is provided, and then add a sodium hydroxide solution to adjust the pH of the system to 5.3 to obtain solution A. Add 3,4-dihydroxyphenylacetic acid HCA to solution A to obtain solution B. Dissolve EDC and NHS in a mixed solvent C composed of distilled water and anhydrous ethanol, and add them dropwise to the above solution B under continuous stirring, ensuring that the pH of solution B is less than 5.5 throughout the process, fully react for 1.5 hours, transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 4000Da for dialysis, and finally freeze-dry the sample at -40°C to obtain the mussel chitosan Cat-CS.
[0060] The concentration of hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:4:4; the degree of grafting of catechol is 8.3%;
[0061] The dialysis conditions were as follows: dialysis in a hydrochloric acid solution with a pH of 3.2 and containing 100 mmol / L NaCl for 36 h, and then dialysis in deionized water for 6 h.
[0062] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS free radical polymerization to prepare thermosensitive polymer PNAM; specifically: dissolve monomers NIPAm and AMPS in mixed solvent D, then add the initiator dropwise to the mixed solvent D under N2 protection and constant temperature stirring at 60°C for 2 hours; after the addition is complete, react for 12 hours, then add 2 mL of initiator, and continue to react for another 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 4000Da, and finally freeze-dried at -40°C to obtain the thermosensitive polymer PNAM.
[0063] The initiator is azobisisoheptanonitrile, the mass of the initiator is 1% of the total mass of the monomers, and the mixed solvent D is deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0064] Step 3, dissolving Cat-CS in deionized water to prepare a Cat-CS solution, preparing a PNAM solution and a NaHCO3 solution; under ice-water bath conditions, sequentially adding PNAM and NaHCO3 solution dropwise to the Cat-CS solution, and stirring for 1 hour, then placing it in a 37°C constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0065] The concentration of Cat-CS solution is 20 mg / mL; the concentration of NaHCO3 solution is 0.08 mol / L; the mass concentration of PNAM aqueous solution is 3.0 mg / mL; the volume ratio of Cat-CS, PNAM and NaHCO3 solution is 15:3:10; the dropping speed is 0.7 μL / s.
[0066] The temperature of the ice water bath was 3°C, the freeze drying temperature was -40°C, the freeze drying time was 12h, the gel time was 50s, and the adhesion strength was 125kPa.
[0067] Example 3
[0068] The present invention relates to a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which is specifically implemented according to the following steps:
[0069] Step 1, dissolve chitosan CS in a hydrochloric acid solution with a pH of 1.7, and add a certain concentration of hydrochloric acid to adjust the pH of the system back to 1.7, so that the chitosan is protonated and an acidic environment is provided, and then add a sodium hydroxide solution to adjust the pH of the system to 5.5 to obtain solution A. Add 3,4-dihydroxyphenylacetic acid HCA to solution A to obtain solution B. Dissolve EDC and NHS in a mixed solvent C composed of distilled water and anhydrous ethanol, and add them dropwise to the above solution B under continuous stirring, ensuring that the pH of solution B is less than 5.5 throughout the process, fully react for 1.2 hours, transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 5000Da for dialysis, and finally freeze-dry the sample at -45°C to obtain mussel chitosan Cat-CS.
[0070] The concentration of hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:6:6; the degree of grafting of catechol is 11.2%;
[0071] The dialysis conditions were as follows: dialysis in a hydrochloric acid solution with a pH of 3.3 and containing 100 mmol / L NaCl for 72 h, and then dialysis in deionized water for 8 h.
[0072] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS free radical polymerization to prepare thermosensitive polymer PNAM; specifically: dissolve monomers NIPAm and AMPS in mixed solvent D, then add the initiator dropwise to the mixed solvent D under N2 protection and constant temperature stirring at 60°C for 3 hours; after the addition is complete, react for 12 hours, then add 2 mL of initiator, and continue to react for another 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 5000Da, and finally freeze-dried at -45°C to obtain the thermosensitive polymer PNAM.
[0073] The initiator is azobisisoheptanonitrile, the mass of the initiator is 1% of the total mass of the monomers, and the mixed solvent D is deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0074] Step 3, dissolving Cat-CS in deionized water to prepare a Cat-CS solution, preparing a PNAM solution and a NaHCO3 solution; under ice-water bath conditions, sequentially adding PNAM and NaHCO3 solution dropwise to the Cat-CS solution, and stirring for 1 hour, then placing it in a 37°C constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0075] The concentration of Cat-CS solution is 20 mg / mL; the concentration of NaHCO3 solution is 0.10 mol / L; the mass concentration of PNAM aqueous solution is 3.0 mg / mL; the volume ratio of Cat-CS, PNAM and NaHCO3 solution is 15:3:10; the dropping speed is 0.8 μL / s.
[0076] The temperature of the ice water bath was 2°C, the gel time was 30s, the adhesion strength was 157kPa, the freeze drying time was 18h, and the freeze drying temperature was -45°C.
[0077] Example 4
[0078] The present invention relates to a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which is specifically implemented according to the following steps:
[0079] Step 1, dissolve chitosan CS in a hydrochloric acid solution with a pH of 1.6, and add a certain concentration of hydrochloric acid to adjust the pH of the system back to 1.6, so that the chitosan is protonated and an acidic environment is provided, and then add a sodium hydroxide solution to adjust the pH of the system to 5.4 to obtain solution A. Add 3,4-dihydroxyphenylacetic acid HCA to solution A to obtain solution B. Dissolve EDC and NHS in a mixed solvent C composed of distilled water and anhydrous ethanol, and add them dropwise to the above solution B under continuous stirring, ensuring that the pH of solution B is less than 5.5 throughout the process, fully react for 1.4 hours, transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 3500Da for dialysis, and finally freeze-dry the sample at -46°C to obtain the mussel chitosan Cat-CS.
[0080] The concentration of hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:4:4; the degree of grafting of catechol is 8.3%;
[0081] The dialysis conditions were as follows: dialysis in a hydrochloric acid solution with a pH of 3.4 and containing 100 mmol / L NaCl for 48 h, and then dialysis in deionized water for 8 h.
[0082] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS free radical polymerization to prepare thermosensitive polymer PNAM; specifically: dissolve monomers NIPAm and AMPS in mixed solvent D, then add the initiator dropwise to the mixed solvent D under N2 protection and constant temperature stirring at 60°C for 2 hours; after the addition is complete, react for 12 hours, then add 2 mL of initiator, and continue to react for another 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da, and finally freeze-dried at -46°C to obtain the thermosensitive polymer PNAM.
[0083] The initiator is azobisisoheptanonitrile, the mass of the initiator is 1% of the total mass of the monomers, and the mixed solvent D is deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0084] Step 3, dissolving Cat-CS in deionized water to prepare a Cat-CS solution, preparing a PNAM solution and a NaHCO3 solution; under ice-water bath conditions, sequentially adding PNAM and NaHCO3 solution dropwise to the Cat-CS solution, and stirring for 2 hours, then placing it in a 37°C constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0085] The concentration of Cat-CS solution is 20 mg / mL; the concentration of NaHCO3 solution is 0.08 mol / L; the mass concentration of PNAM aqueous solution is 2.0 mg / mL; the volume ratio of Cat-CS, PNAM and NaHCO3 solution is 15:3:10; the dropping speed is 0.7 μL / s.
[0086] The temperature of the ice water bath was 4°C, the freeze drying temperature was -46°C, the freeze drying time was 24h, the gel time was 110s, and the adhesion strength was 118kPa.
[0087] Example 5
[0088] The present invention relates to a method for preparing an injectable mussel shell polysaccharide hydrogel adhesive, which is specifically implemented according to the following steps:
[0089] Step 1, dissolve chitosan CS in a hydrochloric acid solution with a pH of 1.5, and add a certain concentration of hydrochloric acid to adjust the pH of the system back to 1.5, so that the chitosan is protonated and an acidic environment is provided, and then add a sodium hydroxide solution to adjust the pH of the system to 5.4 to obtain solution A. Add 3,4-dihydroxyphenylacetic acid HCA to solution A to obtain solution B. Dissolve EDC and NHS in a mixed solvent C composed of distilled water and anhydrous ethanol, and add them dropwise to the above solution B under continuous stirring, ensuring that the pH of solution B is less than 5.5 throughout the process, fully react for 1.5 hours, transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 3500Da for dialysis, and finally freeze-dry the sample at -43°C to obtain mussel chitosan Cat-CS.
[0090] The concentration of hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is distilled water and anhydrous ethanol in a volume ratio of 1:1; the molar ratio of CS, HCA, EDC, and NHS is 1:2:4:4; the degree of grafting of catechol is 8.3%;
[0091] The dialysis conditions were as follows: dialysis in a hydrochloric acid solution with a pH of 3.5 and containing 100 mmol / L NaCl for 48 h, and then dialysis in deionized water for 8 h.
[0092] Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS free radical polymerization to prepare thermosensitive polymer PNAM; specifically: dissolve monomers NIPAm and AMPS in mixed solvent D, then add the initiator dropwise to the mixed solvent D under N2 protection and constant temperature stirring at 60°C for 3 hours; after the addition is complete, react for 12 hours, then add 2 mL of initiator, and continue to react for another 12 hours. The reaction solution is dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da, and finally freeze-dried at -43°C to obtain the thermosensitive polymer PNAM.
[0093] The initiator is azobisisoheptanonitrile, the mass of the initiator is 1% of the total mass of the monomers, and the mixed solvent D is deionized water and 1,4-dioxane, and the volume ratio is 4:1.
[0094] Step 3, dissolving Cat-CS in deionized water to prepare a Cat-CS solution, preparing a PNAM solution and a NaHCO3 solution; under ice-water bath conditions, sequentially adding PNAM and NaHCO3 solution dropwise to the Cat-CS solution, and stirring for 2 hours, then placing it in a 37°C constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel.
[0095] The concentration of Cat-CS solution is 20 mg / mL; the concentration of NaHCO3 solution is 0.08 mol / L; the mass concentration of PNAM aqueous solution is 5.0 mg / mL; the volume ratio of Cat-CS, PNAM and NaHCO3 solution is 15:3:10; the dropping speed is 0.9 μL / s.
[0096] The temperature of the ice water bath was 2°C, the freeze drying temperature was -43°C, the freeze drying time was 24h, the gel time was 60s, and the adhesion strength was 120kPa.
Claims
1. A method for preparing an injectable mussel shell polysan hydrogel adhesive, characterized in that: Follow the steps below to implement it: Step 1, using chitosan CS as a matrix, and adopting a carbodiimide coupling method to prepare mussel biomimetic modified chitosan Cat-CS; The step 1 is specifically implemented according to the following steps: The chitosan CS is dissolved in a hydrochloric acid solution, and the pH is adjusted to 1.5-1.7, and then a sodium hydroxide solution is added to adjust the pH to 5.3-5.5 to obtain a solution A, 3,4-dihydroxyphenylacetic acid HCA is added to the solution A to obtain a solution B, 1-ethyl-(3-dimethylaminopropyl) carbodiimide EDC and N-hydroxysuccinimide NHS are dissolved in a mixed solvent C, and are added dropwise to the solution B under continuous stirring, and fully reacted for 1-2 hours, and the fully reacted solution is dialyzed, and finally freeze-dried at -40--50°C to obtain the mussel chitosan Cat-CS; In step 1, the concentration of hydrochloric acid is 1 mol / L, and the concentration of sodium hydroxide solution is 1 mol / L; the mixed solvent C is composed of distilled water and anhydrous ethanol, and the volume ratio is 1:1; The molar ratio of CS, HCA, EDC, and NHS is 1:2:1:1 to 1:2:8:8; The dialysis conditions in step 1 are: dialyzing in a hydrochloric acid solution containing 100 mmol / L NaCl for 48 to 72 hours, the pH of the hydrochloric acid solution is 3 to 3.5, and then dialyzing in deionized water for 4 to 8 hours. In step 1, the fully reacted solution is transferred to a dialysis bag with a molecular weight cutoff of 3500 to 5000 Da for dialysis; Step 2, using N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS as monomers, a free radical solution polymerization method is used to prepare a thermosensitive polymer PNAM; The step 2 is specifically implemented according to the following steps: The monomers N-isopropylacrylamide NIPAm and 2-acrylamido-2-methylpropanesulfonic acid AMPS were dissolved in a mixed solvent D, and the initiator was added dropwise under N2 protection and constant temperature stirring for 2 to 3 hours at a reaction temperature of 55 to 65°C; after the addition was completed, 2 mL of initiator was added after reacting for 10 to 12 hours, and the reaction was continued for another 10 to 12 hours, and the reaction solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da, and finally freeze-dried at -40 to -50°C to obtain a thermosensitive polymer PNAM; In step 2, the initiator is azobisisoheptanenitrile, and the mass of the initiator is 1% of the total mass of N-isopropylacrylamide NIPAm and 2-acrylamide-2-methylpropanesulfonic acid AMPS monomers; the mixed solvent is composed of deionized water and 1,4-dioxane, and the volume ratio is 4:1; Step 3, dissolving Cat-CS in deionized water to prepare a mussel biomimetic modified chitosan Cat-CS solution, and then preparing a PNAM solution and a NaHCO3 solution; under ice water bath conditions, sequentially adding the PNAM solution and the NaHCO3 solution dropwise to the mussel biomimetic modified chitosan Cat-CS solution, continuously stirring, then placing in a constant temperature water bath to form a hydrogel adhesive, and finally freeze-drying to obtain a xerogel; In step 3: The concentration of mussel biomimetic modified chitosan Cat-CS solution is 10-35 mg / mL; the concentration of NaHCO3 solution is 0.06-0.10 mol / L; the mass concentration of PNAM aqueous solution is 2.0-6.0 mg / mL; the volume ratio of mussel biomimetic modified chitosan Cat-CS solution, PNAM solution and NaHCO3 solution is 15:3:10; In step 3, the temperature of the ice water bath is 0-4° C., the dropping speed is 0.5-1.0 μL / s, the stirring time is 1-2 h, the freeze drying temperature is -40--50° C., the freeze drying time is 12-24 h, and the gel time is 30-180 s.
Citation Information
Patent Citations
Mussel-imitated underwater high-viscosity hydrogel preparation method
CN110684212A
Preparation method and application of implantable in-situ formed chitosan hydrogel
CN112807439A